Nursing practice environment, resilience, and intention to leave among critical care nurses. Issue 6 (14th September 2020) - Ying, Luk Ying; Ramoo, Vimala; Ling, Lee Wan; Nahasaram, Sri Theyshaini; Lei, Chui Ping; Leong, Luk Kuok; Danaee, Mahmoud
Abstract: Background: Retaining experienced critical care nurses (CCNs) remains a challenge for health care organizations. Nursing practice environment and resilience are both seen as modifiable factors in ameliorating the impact on CCNs' intention to leave and have not yet been explored in Malaysia. Aims and objectives: To assess the association between perceived nursing practice environment, resilience, and intention to leave among CCNs and to determine the effect of resilience on intention to leave after controlling for other independent variables. Design: This was a cross‐sectional survey. Methods: The universal sampling method was used to recruit nurses from adult and paediatric (including neonatal) critical care units of a large public university hospital in Malaysia. Descriptive analysis and χ 2 and hierarchical logistic regression tests were used to analyse the data. Results: A total of 229 CCNs completed the self‐administrated questionnaire. Of the nurses, 76.4% perceived their practice environment as being favourable, 54.1% were moderately resilient, and only 20% were intending to leave. The logistic regression model explained 13.1% of variance in intention to leave and suggested that being single, an unfavourable practice environment, and increasing resilience were significant predictors of nurses' intention to leave. Conclusion: This study found that an unfavourable practice environment is a strong predictor of intention to leave; however, further exploration is needed to explain the higher likelihood of expressing intention to leave among CCNs when their resilience level increases. Relevance to clinical practice: Looking into staff allocation and equality of workload assignments may improve the perception of the work environment and help minimize intention to leave among nurses.